Resolving Crimes of Domestic Violence Through Restorative Justice - Ramadhan, Sagita Destia (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2024)
Restorative Justice is a form of resolving criminal cases non-litigation or outside of court. However, not all crimes can be resolved through restorative justice. In several regulations, it is explained that criminal acts that can be resolved through this settlement are minor crimes with one of the criteria being imprisonment for more than five years. So in this case Domestic Violence can be resolved because in accordance with Law Number 23 of 2004 concerning the Elimination of Domestic Violence, domestic violence is punishable by a maximum of five years. In restorative justice, it is known as returning to the original state. Here the author criticizes that domestic violence should not be included in restorative justice solutions because domestic violence is considered a physical crime by criminal law, the victim here suffers from physical and even psychological injuries. And these wounds will be a trauma forever for the victim. The type of research carried out by the author is normative research in which data collection is carried out by searching literature such as statutory regulations, written.